2017
DOI: 10.1111/evj.12716
|View full text |Cite
|
Sign up to set email alerts
|

Equine meniscal degeneration is associated with medial femorotibial osteoarthritis

Abstract: This study is the first to describe normal equine meniscal morphology and lesions. Meniscal lesions were identified in all segments and on both articular surfaces. Meniscal degeneration significantly correlated with OA severity in the equine medial femorotibial joint. The relationship between OA and meniscal pathology remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Meniscal injury has been associated with equine medial femorotibial disease, including MFC SBCs both before and after treatment . This is the first report examining the mechanical impact of a MFC void on the equine meniscus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Meniscal injury has been associated with equine medial femorotibial disease, including MFC SBCs both before and after treatment . This is the first report examining the mechanical impact of a MFC void on the equine meniscus.…”
Section: Discussionmentioning
confidence: 93%
“…We believe that the changes in the meniscus stress that occur with an MFC SBC may explain some meniscal injuries because our model predicts an increase of about 30% in peak tension and shear on the meniscus when an MFC void is present. This increase in stress occurs in the meniscal body, a common location of injury (Figure ), and may be exacerbated when the loaded stifle is flexed . Two previous studies have measured contact pressure ex vivo on the proximal tibia under the equine medial meniscus, but they did not agree on the shape of the pressure maps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it is di cult to obtain enough pathological tissues in small animals (mouse, rat, and rabbit), particularly on an eroded cartilage surface. However, large animals (horse and bovid) are di cult to manage and breed [6,7]. Diannan small-ear pig is a kind of mini pig produced in Yunnan with the average maturation age of 8 months.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that meniscal lesions were identified in all segments of this structure, and affected both articular surfaces. A significant association was demonstrated between meniscal degeneration and OA severity, however, the relationship between OA and meniscal pathology remains to be elucidated [24].…”
mentioning
confidence: 98%